2020
DOI: 10.1101/2020.06.29.175968
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zonal human hepatocytes are differentially permissive toPlasmodium falciparummalaria parasites

Abstract: AbstractPlasmodium falciparum (Pf) is a major cause of malaria. The mosquito-borne parasite asymptomatically infects hepatocytes in the liver. The resulting schizonts undergo massive replication to generate blood-infective merozoites. Liver lobules are zonated: hepatocytes in different zones perform differential metabolic functions. In search for specific host conditions that affect infectability, we studied the Pf parasite … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Periportal hepatocytes engage in protein secretion, ureagenesis and gluconeogenesis, whereas pericentral hepatocytes specialize in processes such as bile acid production, xenobiotic metabolism and glutamine biosynthesis 3 . Previous ex-vivo studies suggested that the pace of Plasmodium infection could differ between pericentral and periportal hepatocytes 9,10 . Studies using bulk RNA measurements characterized the transcriptomes of host and parasite during the liver stage of infection 11,12 , and a malaria single cell atlas was generated using an ex-vivo platform 13 .…”
Section: Mainmentioning
confidence: 99%
“…Periportal hepatocytes engage in protein secretion, ureagenesis and gluconeogenesis, whereas pericentral hepatocytes specialize in processes such as bile acid production, xenobiotic metabolism and glutamine biosynthesis 3 . Previous ex-vivo studies suggested that the pace of Plasmodium infection could differ between pericentral and periportal hepatocytes 9,10 . Studies using bulk RNA measurements characterized the transcriptomes of host and parasite during the liver stage of infection 11,12 , and a malaria single cell atlas was generated using an ex-vivo platform 13 .…”
Section: Mainmentioning
confidence: 99%
“…An additional limitation is that the current study stopped when oocysts were detected in the mosquito midgut. For a number of isolates data on sporozoite production are also available [13,14] but comparing sporozoite production or infectivity between individual isolates was beyond the scope of this manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of genetic variation for vaccine and drug e cacy, reliance on a single parasite isolate fails to give a comprehensive insight into intervention potency in natural infections [10]. Similarly, relevant inter-strain variation in parasite growth rates [11], gametocyte production [12] and sporozoite invasion capacity [13,14] warrant further examination. The current portfolio of laboratory isolates for studies on sexual and sporogonic stages is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the process for manufacturing cryo-plateable lots of primary hepatocytes could affect cell phenotypes, including the aforementioned surface receptors, and alter hepatocyte permissiveness [18,19]. Host cell permissiveness is likely also modulated by host cell environment as sufficient glycolytic and respiratory activities are needed to sustain the energy demands of an intracellular parasite [20][21][22]. As such, liver lobules perform different metabolic functions and have recently been shown to influence P. falciparum parasite preferences and growth in the host cell [22].…”
Section: Introductionmentioning
confidence: 99%